Impact of illegal urban agricultural activities on bio-diversity of Emakhandeni high density suburb of Bulawayo, Zimbabwe - Banga, Patrick F. (Midlands State University, 2015)
This paper examines the impact of unsanctioned urban agricultural activities in Emakhandeni High Density Suburb of Bulawayo and its periphery and their implications for climate change and global warming. The researchers adopted the purposive sampling technique to interview100 people who engage inillegal agricultural activities in Emakhandeni and its periphery, employees of Bulawayo City Council, the Local councillor and ward committee members. Field visits were also carried out to observe the impacts of unsanctioned agricultural activities on bio-diversity of Emakhandeni. The findings were that in spite of the existence of City Council ByLaws on Urban Agriculture and an Urban Agriculture Policy which was incorporated into the Bulawayo City Council Master Plan (2006-2015) the majority of the cultivators are operating outside these laws and guidelines. People both from Emakhandeni and other surrounding suburbs have parcelled out every available open space of land in Emakhandeni and its periphery and are engaging in unsustainable farming and animal husbandry practices, leading to progressive land degradation. There is massive deforestation which increases levels of carbon dioxide in the atmosphere owing to increased use of diesel driven generators and firewood due to electricity loadshedding. Stream-bank and slope cultivation is rife leading to massive soil erosion and siltation. Parches of cultivated wet lands have dried up thereby driving the water table lower in an already dry region, thereby increasing aridity. The use of pesticides and inorganic fertilisers is compromising ground water quality and threatening survival of flora and fauna downstream. It is recommended that politicisation of urban agriculture should be avoided to allow city fathers to actively supervise and monitor urban agricultural activities in Emakhandeni. This would minimise negative impacts on the local and down-stream environments thereby enhancing sustainable land use patterns and thus help reduce their negative contributions to climate change and global warming.